Evolution and challenges of sport policy in Lithuania: a historical and contemporary analysis - Mikalauskas, Rimantas; Valantine, Irena; Begović, Marko (Frontiers in Sports and Active Living, 2025)
IntroductionThis paper examines the evolution and contemporary challenges of sport policy in Lithuania, emphasizing the interplay between politics and national planning. It provides a historical overview of Lithuanian sport policy development, particularly focusing on the transition from the Soviet system to a democratic model after regaining independence in 1990. Key components, stakeholders, and the structure of the current Lithuanian sport system are analyzed, highlighting the critical role of sports science. The study identifies significant gaps in academic research on sport policy and underscores the necessity for more comprehensive studies in this field. It discusses the main challenges influencing the future of Lithuanian sport policy, including political instability, bureaucratic influence, and limited stakeholder involvement. The purpose of this paper is to address a gap in the academic literature and enhance the scientific understanding of sport policy development in Lithuania. Accordingly, this study seeks to answer the following research question: How has Lithuanian sport policy evolved since independence, and what political and institutional factors currently shape its development and implementation? By exploring this question, the study aims to fill a notable gap in academic literature and contribute to a deeper understanding of sport governance in post-socialist European contexts.MethodsThe study applies a qualitative document based analysis covering Lithuanian sport policy from 1990-2025.ResultsThe findings reveal that Lithuanian sport policy remains highly centralized and politically influenced, with fragmented governance and limited stakeholder involvement.DiscussionThe study concludes with a call for a unified long-term national strategy, transparent funding mechanisms, and evidence-based policymaking to strengthen future sport governance.